Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Use the given conditions to write an equation for the line in point-slope form and in slope-intercept form.

Given:
- Slope [tex]\( m = -\frac{1}{6} \)[/tex]
- Passing through the point [tex]\((4, -2)\)[/tex]

Write an equation for the line in point-slope form.

[tex]\[ y - y_1 = m(x - x_1) \][/tex]

Solution:
[tex]\[ y + 2 = -\frac{1}{6}(x - 4) \][/tex]

(Simplify your answer. Use integers or fractions for any numbers in the equation.)


Sagot :

To determine the equation of the line using the given conditions – a slope of [tex]\(-\frac{1}{6}\)[/tex] and the point [tex]\((4, -2)\)[/tex] – we will proceed in two parts.

### Part 1: Point-Slope Form

The point-slope form of a linear equation is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]

Here, [tex]\( m \)[/tex] is the slope, and [tex]\( (x_1, y_1) \)[/tex] is the point through which the line passes.

Given:
- Slope [tex]\( m = -\frac{1}{6} \)[/tex]
- Point [tex]\( (x_1, y_1) = (4, -2) \)[/tex]

Plug these values into the point-slope form formula:
[tex]\[ y - (-2) = -\frac{1}{6}(x - 4) \][/tex]

Simplify the left side:
[tex]\[ y + 2 = -\frac{1}{6}(x - 4) \][/tex]

So, the equation of the line in point-slope form is:
[tex]\[ y + 2 = -\frac{1}{6}(x - 4) \][/tex]

### Part 2: Slope-Intercept Form

The slope-intercept form of a linear equation is given by:
[tex]\[ y = mx + b \][/tex]

We start with the point-slope form equation obtained:
[tex]\[ y + 2 = -\frac{1}{6}(x - 4) \][/tex]

Expand the right side:
[tex]\[ y + 2 = -\frac{1}{6}x + \frac{4}{6} \][/tex]

Simplify the constant term on the right side:
[tex]\[ y + 2 = -\frac{1}{6}x + \frac{2}{3} \][/tex]

Next, subtract 2 from both sides to solve for [tex]\( y \)[/tex]:
[tex]\[ y = -\frac{1}{6}x + \frac{2}{3} - 2 \][/tex]

Convert -2 to fractions to combine with [tex]\(\frac{2}{3}\)[/tex]:
[tex]\[ y = -\frac{1}{6}x + \frac{2}{3} - \frac{6}{3} \][/tex]

Subtract [tex]\(\frac{6}{3}\)[/tex] from [tex]\(\frac{2}{3}\)[/tex]:
[tex]\[ y = -\frac{1}{6}x - \frac{4}{3} \][/tex]

Thus, the equation of the line in slope-intercept form is:
[tex]\[ y = -\frac{1}{6}x - \frac{4}{3} \][/tex]

In summary:
- Point-slope form: [tex]\( y + 2 = -\frac{1}{6}(x - 4) \)[/tex]
- Slope-intercept form: [tex]\( y = -\frac{1}{6}x - \frac{4}{3} \)[/tex]